Cytokines and Chemokines as Biomarkers of Future Asthma - Bush, Andrew (Frontiers in Pediatrics, 2019)
Antenatal and preschool factors are key in determining the progression to pre-school wheeze and eosinophilic school age asthma. The conventional view of eosinophilic asthma is that airway inflammation is the fundamental underlying abnormality, and airway inflammation and hyper-responsiveness are secondary; in fact, these three are parallel processes. Very early structural changes, independent of inflammation and infection, are associated with early airway hyper-responsiveness and later adverse respiratory outcomes. There is a bidirectional relationship between structural airway wall changes and airway inflammation, with airway contraction per se leading to the release of growth factors, and inflammatory pathways promoting airway remodelling. Early viral infection (and increasingly being appreciated, bacterial infection) is important in wheeze outcomes. There is evidence of abnormal immune function including cytokine release before the onset of viral infections. However, viral infections may also have prolonged effects on the host immune system, and the evidence for beneficial and adverse effects of viral infection is conflicting. In older children and adults, asthmatic epithelial cells show impaired interferon responses to viral infection, but only in the presence of uncontrolled type 2 inflammation, implying these are secondary phenomena. There are also compelling data relating the innate immune system to later asthma and atopy, and animal studies suggest that the effects of a high endotoxin, microbiologically diverse environment may be modulated via the epithelial alarmin IL-33. Whereas previously only viral infection was thought to be important, early bacterial colonisation of the upper airway is coming to the fore, associated with a mixed pattern of TH1/TH2/TH17 cytokine secretion, and adverse long term outcomes. Bacterial colonisation is probably a marker of a subtle immune deficiency, rather than directly causal. The airway and gut microbiome critically impacts the development of Type 2 inflammatory responses. However, Type 2 inflammatory cytokines, which are critical both to progression from pre-school wheeze to eosinophilic asthma, and sustaining the eosinophilic asthmatic state, are not implicated in the very early development of the disease. Taken together, the evidence is that the earliest cytokine and chemokine signals will come from the study of bronchial epithelial cell function and their interactions with viruses and the microbiome.